PENERAPAN MODEL PEMBELAJARAN SCRAMBLE TERHADAP PENINGKATAN HASIL BELAJAR BIOLOGI SISWA DI KELAS X SMA YAYASAN PERGURUAN KELUARGA PEMATANGSIANTAR - Rajagukguk, Salome (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2021)
This study is a classroom action research aimed at describing the application of the Scramble model to improve biology learning outcomes at the Yayasan Perguruan Keluarga Private High School in Pematangsiantar. The subjects were 30 students in grade X IPA-1 at the Yayasan Perguruan Keluarga Private High School. The study was conducted in four stages: planning, implementation, observation, and reflection. This Classroom Action Research (CAR) used a collaborative model that prioritizes cooperation between teachers and researchers. The instrument used in this study was a 20-question student learning achievement test. Before being used as a data collection tool, the prepared instrument was pre-tested to determine its validity, reliability, discrimination power, and difficulty level. Based on the results, the average improvement in students' critical thinking skills was 60.00 in cycle I, then increased to 80.00 in cycle II. From these results, it can be concluded that the application of the Scramble learning model can improve student learning outcomes in grade X SMA YPK Pematangsiantar.